(untitled) (Research, Society and Development, 2023)
Aim: To report university extension activities for university employees in time of Covid-19 pandemic. Methods: Technical workers from diferent sectors from a Campus of a Public University were selected, and personal, work and contact data were obtained. Workers were invited to participate in conversation circles held via Google Meet, on the topic of telework and health. The Mentimeter plataforma was used for topics that triggered conversations, and the subjects were discussed and registered by the students. Results: Twenty-one servants of both sexes participated, and eight meetings were held, the last one was feedback. After de debates, negative aspects of telework emerged, as: loneliness/isolation, need to adapt, organizing tasks between work and household chores, tiredness, work overload, among others. The main positive aspects: flexibility, more free time, among others. Conclusion: The meetings provided reflections, learning and exchange of experiences, highlighting the need for health care in this type of work.